2023
DOI: 10.3390/en16031267
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Distributed Generation on the Operation of the Power System, Based on the Example of PV Micro-Installations

Abstract: This article describes the problems associated with distributed electrical power generation and the most frequent interruptions occurring in power grids. The most common methods of improving the quality of the power supply were analyzed and the possibilities offered by energy storages in this respect were considered. The operating parameters of an exemplary PV system connected to the power grid were analyzed. For this purpose, the model implemented in the Matlab/Simulink environment was used. Based on the cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…According to the Polish grid connection codes [4], the installation of PV panels with capacity up to the customer's contracted power does not require the permission of the distributed network operator (DSO), and so, the network hosting capacity is not verified. In these conditions, the high penetration of PV sources may negatively affect the network operating conditions and result in deterioration of the quality of the energy delivered to end-users [5][6][7][8][9]. One of the most serious threats is an excessive voltage rise in the network nodes caused by the change of electricity flow during periods of high PV generation when Energies 2024, 17, 1594 2 of 12 excess power in the prosumer installation is introduced to the network.…”
Section: Introductionmentioning
confidence: 99%
“…According to the Polish grid connection codes [4], the installation of PV panels with capacity up to the customer's contracted power does not require the permission of the distributed network operator (DSO), and so, the network hosting capacity is not verified. In these conditions, the high penetration of PV sources may negatively affect the network operating conditions and result in deterioration of the quality of the energy delivered to end-users [5][6][7][8][9]. One of the most serious threats is an excessive voltage rise in the network nodes caused by the change of electricity flow during periods of high PV generation when Energies 2024, 17, 1594 2 of 12 excess power in the prosumer installation is introduced to the network.…”
Section: Introductionmentioning
confidence: 99%
“…It is obvious that these phenomena negatively affect power quality (PQ), result in additional power and energy losses, and can cause disruptions in the operation of prosumer installations and the supplying network [8][9][10][11][12]. A major problem for prosumers is switching-off the PV inverters due to the effect of unacceptable voltage rise [7,13].…”
Section: Introductionmentioning
confidence: 99%
“…Research conducted in France and Belgium on more than 10,000 systems has demonstrated lower micro-system efficiency by 16% [1]. Therefore, optimizing the energy efficiency of PV micro-systems, which should be taken into account not only at the engineering stage but also during operation, is an important aspect [2][3][4]. Maintaining the highest efficiency level of PV systems throughout their operation requires reliable and rapid servicing and diagnosing [5][6][7].…”
Section: Introductionmentioning
confidence: 99%